SYNTHESIS OF ANTHRAQUINONE DERIVATIVES AND THEIR ANTIBACTERIAL ACTIVITY - Nurbayti, Siti
Anthraquinone is a group of aromatic compounds based on 9,10-anthracendione skeleton. In nature, anthraquinones have been found in a number of organisms, including plants, bacteria, fungi, and insects. People has known anthraquinones for a long time ago because these groups are widely distributed in organisms, and therefore they have been used as a source of pigments, as well as in traditional medicines. Decoctions of anthraquinones-bearing plants (leaves, tree or root barks) have been used to alleviate heart problems, arthritis, gallstones, tuberculosis, and skin infections. Biological evaluations have also been done towards pure compounds of anthraquinones against a number of biological targets, including targets as antioxidants, anticancer, antimalaria, antivirus, and antibacteria. The latter gave a promising results as some of the compounds exhibited MIC values less than 10 ?g/mL. These data showed that anthraquinones are potential candidates to be developed as antibacterial agents. Therefore, developing a series of anthraquinone derivatives is an important research so that more knowledge of the antibacterial properties of these compounds will be gathered. This research is aimed to syntheses of anthraquinone derivatives and to evaluate their antibacterial properties. Twenty two anthraquinone derivatives based on 1,2- dihydroxyanthraquinone (alizarin), 1,3-dihydroxyanthraquinone (xanthopurpurin), and 1,3,5,7-tetrahydroxyanthraquinone (anthrachrysin) have been succesfully synthesized. 1,3,5,7-Tetrahydroxy-anthraquinone was prepared by a symmetric condensation of 3,5-dihydroxybenzoic acid in concentrated H2SO4 under reflux condition. With the same method, 1,3-dihydroxyanthraquinone was also prepared from 3,5-dihydroxybenzoic acid and benzoic acid. The three anthraquinones were then converted O- dan C-prenylated, O-benzylated, O-benzoylated, O-acetylated, O-methylated, and O-silylated antraquinone derivatives, as well as a reduced derivative of 1,3,5,7-tetrahydroxyanthraquinone (1,3,5,7-tetrahydroxyanthrone). These derivative compounds were purified through extraction and purification steps using various chromatographic techniques. Identification and structure elucidation were undertaken based on NMR (1D and 2D) and high resolution mass spectral data. Antibacterial testing was carried out against four clinical isolates of pathogenic bacteria, including Escherichia coli, Salmonella typhi, Bacillus subtilis, and Staphylococcus aureus, using a microdilution method. The twenty two derivatives were 2-acetoxy-1-hydroxyanthraquinone (1), 1,2-di acetoxyanthraquinone (2), 1,2-bis(benzoyloxy)anthraquinone (3), 1-hydroxy-2- prenyloxyanthraquinone (4), 1,3-dihydroxyanthraquinone (5), 1,3-bis- (benzoyloxy)anthraquinone (6), 2-benzoyloxy-4-hydroxy-9-oxo-9,10-dihydroanthracene (7), 1-hydroxy-3-prenyloxyanthraquinone (8), 1,3-diprenyloxyanthraquinone (9), 1-acetoxy-3-prenyloxyanthraquinone (10), 1,3,5,7- tetrahydroxyanthraquinone (11), 1,3,5,7-tetrahydroxy-9-oxo-9,10-dihydroanthracene (12), 1-hydroxy-3,5,7,9-tetramethoxyanthracene (13), 1,3,5- trihydroxy-7-methoxyanthraquinone (14), 1-hydroxy-3,5,7-trimethoxyanthraquinone (15), 3-benzyloxy-1,5,7-trihydroxyanthraquinone (16), 1,3,7- tris(benzyloxy)-5-hydroxyanthraquinone (17), 3-(tert-butyldimethylsilyloxy)- 1,5,7-trihydroxyanthraquinone (18), 3,7-bis(tert-butyldimethylsilyloxy)-1,5- dihydroxyanthraquinone (19), 1-hydroxy-3,5,7-triprenyloxyanthraquinone (20), 1,5-dihydroxy-2-prenyl-3,7-diprenyloxyanthraquinone (21) and 1-benzoyloxy- 3,5,7-tris(benzyloxy)anthraquinone (22). Compounds 4, 6-10, 13, and 16-22 are new chemical compounds. Antibacterial evaluation showed that compounds 1, 4, and 16 exhibited moderate activities against E. coli with MIC and MBC values of 37.5 and 75 ?g/mL, respectively. Compounds 6, 9, and 20 also showed moderate activities against two bacteria S. aureus and E. coli with MIC and MBC values of 37.5 and 75-150 ?g/mL, respectively. Compound 2, however, was active against S. aureus, E. coli, and S. typhi (MIC 37.5 ?g/mL; MBC 75-150 ?g/mL). Compounds 8 and 12 were active only against S, aureus, while compound 10 against B. subtilis and S. aureus, compound 13 against S. aureus, E. coli, and S. typhi, and compound 22 against B. subtilis and E. coli. The rest ten anthraquinone compounds were only exhibited weak activities against the four tested bacteria (MIC 75-150 ?g/mL).